Relationship status and health: does the use of different relationship indicators matter? - Schneider, Björn; Rapp, Ingmar; Klein, Thomas; Eckhard, Jan (Global public health, 2014)
Studies that analyse the association between relationship status and health usually disregard non-marital relationships. The present study examines if the use of different relationship indicators leads to different associations between relationship status and physical and mental health. The database used for this analysis is the Survey of Health and Ageing in Europe, a large population-based survey of Europeans aged 50 and over and their cohabitants. This study combines cross-sectional and retrospective data of 13 European countries. The sample size is 9298 men and 11,631 women for grip strength and 9609 men and 12,333 women for depression. Generalised estimating equations are used. For men, the goodness-of-fit measure quasi-likelihood under the independence model criterion indicates that marital status is a better predictor than cohabitation status or partnership status for predicting grip strength. However, for grip strength of women, there are only small differences in the model fit between the different relationship indicators. For both men and women, the partnership status (marriage, cohabitation or dating relationship) shows the best model fit for explaining depression. The results suggest that future health research could benefit from the use of relationship indicators other than marital status, particularly regarding mental health.